Preparation method of wrinkled ceramic nanosheet

Through ion exchange and high-temperature treatment, uniform and controllable pleated ceramic nanosheets were successfully prepared, solving the problems of complex processes and high costs in the prior art, and achieving efficient and stable nanosheet preparation.

CN119503846APending Publication Date: 2025-02-25OCEAN UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411650750.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare uniform and controllable pleated nanosheets, and the process is complex and costly, so it has failed to achieve efficient preparation of pleated nanosheets.

Method used

By ion exchange and high-temperature treatment, the polyimide film is treated with sodium hydroxide solution and metal salt solution to form a ceramic oxide metal film to realize the preparation of wrinkled ceramic nanosheets.

Benefits of technology

The uniform controllable preparation of wrinkled ceramic nanosheets is achieved, the process is simplified, the cost is reduced, the quality stability of nanosheets is improved, and the mass production is facilitated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503846A_ABST
    Figure CN119503846A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of wrinkled nanosheets, and particularly relates to a preparation method of a wrinkled ceramic nanosheet. The ultra-thin and ultra-large-area wrinkled ceramic nanosheet is obtained by utilizing ion exchange and high-temperature treatment methods, the preparation process is uniform and controllable, the method is simple, the cost is low, and the prepared nanosheet is stable in quality and is introduced into a polymer dielectric medium as a filler, so that the dielectric constant and the breakdown strength are synergistically improved; the prepared Al2O3 nanosheet is introduced into a polymer as a filler to form a nano composite film, and the breakdown strength at room temperature, 150 DEG C and 200 DEG C is remarkably improved, can reach 780 MV / m, 735 MV / m and 680 MV / m at most, and is equivalent to 144%, 163% and 170% of that of a pure polymer. The method is high in universality, various nanosheets with different metal oxides and similar shapes can be prepared according to metal activity, and batch production can be achieved conveniently.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wrinkled nanosheet preparation, and in particular relates to a method for preparing a wrinkled ceramic nanosheet. Background Art

[0002] Nanosheets are a two-dimensional structure. Two-dimensional ceramic nanosheets belong to the intersection of nanomaterials and advanced ceramic technology. This field involves the study of the structure, properties and applications of nanoscale materials, including the preparation, modification and application of materials at the nanoscale, focusing on the size effect and surface effect of materials. At the same time, the high temperature stability, corrosion resistance and mechanical properties of ceramic materials are studied. Two-dimensional ceramic nanomaterials have excellent mechanical, electrical, thermal and chemical properties and are often used in functional materials. For example, two-dimensional ceramic nanosheets are widely used in energy storage devices, especially in batteries and supercapacitors. Due to their high conductivity and ion transport channels, they can significantly improve the specific capacity, cycle life and charge and discharge speed of batteries. Specific applications include as electrode materials in batteries and electrode materials in supercapacitors to improve electrochemical performance and energy density. In addition, it also includes dielectric energy storage materials. At the same time, two-dimensional ceramic nanosheets as catalysts or catalyst carriers have excellent catalytic activity, high temperature resistance and corrosion resistance. They are widely used in electrocatalysis, photocatalysis and thermal catalysis, including: electrocatalysts in water decomposition to produce hydrogen, catalysts for carbon dioxide reduction reactions, and photocatalysts in the degradation of organic pollutants.

[0003] Due to their high surface area and surface activity, two-dimensional ceramic nanosheets are also suitable as core materials for gas sensors and chemical sensors for detecting gas molecules, chemicals or environmental changes. Specific applications include gas sensors (for detecting harmful gases such as hydrogen, carbon dioxide, ammonia, etc.) and biosensors (for detecting biological molecules, pathogens or biochemical indicators).

[0004] Nanosheets have a wide range of applications in many fields due to their unique structure and properties, including catalysis, medicine, energy storage, etc. Therefore, researchers in various fields have proposed various design strategies for nanosheets.

[0005] For example, the polyimide dielectric nanocomposite prepared by Xi'an Jiaotong University using in-situ polymerization is composed of easily prepared magnesium oxide fillers with different morphologies such as nanoparticles (0D), nanowires (1D) and nanoplates (2D). The results show that two-dimensional nanosheets have a more significant enhancement effect on the energy storage performance of composite materials compared with zero-dimensional nanoparticles and one-dimensional nanowires. Zeng et al. successfully prepared a manganese dioxide ultra-thin film with a wide near-infrared light response range and a degradation rate that varies with pH. Based on polyethylene glycol-cycloarginine-aspartic acid tripeptide, manganese dioxide is used as a photothermal agent, and dihydrochlorin Ce6 is encapsulated with a nano-drug delivery system to achieve targeted photothermal therapy and photodynamic therapy of tumors. The study found that MnO 2 -PEG-cRGD has a high Ce6 loading capacity (351 mg·g -1 ), high photothermal conversion efficiency (37.2%), and high stability. It can be seen that nanosheets also play an indispensable role in the medical field.

[0006] Research has shown that nanosheets have important applications in many fields. Wrinkled nanosheets have a high aspect ratio and a larger surface area than ordinary flat nanosheets. However, most of the nanosheets reported so far use hydrothermal synthesis, which has problems such as complex preparation process, poor repeatability, and unsatisfactory uniformity. In addition, no method for preparing wrinkled nanosheets has been found in the currently reported process flow. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing wrinkled ceramic nanosheets, which uses ion exchange and high temperature treatment methods to achieve the preparation of uniform and controllable wrinkled nanosheets. The preparation method is simple and low in cost. The technical solution adopted is:

[0008] A method for preparing a wrinkled ceramic nanosheet comprises the following steps:

[0009] (1) Cut the polyimide (PI) film into square pieces, clean the surface, remove impurities and set aside;

[0010] (2) Using polyimide film as the matrix, immerse the polyimide film in a sodium hydroxide solution to open the imide ring on the polyimide surface and convert the Na + The polyimide film is then washed with water and immersed in a metal salt solution for ion exchange to introduce metal ions into the film surface;

[0011] (3) Cleaning: The film finally obtained in step (2) is dried and heated from room temperature to 250-350°C at a rate of 1-3°C / min and kept at that temperature for 20-40 minutes to facilitate the formation of a ceramic metal oxide film. The temperature is then raised to 500-700°C at a rate of 4-6°C / min and kept at that temperature for 60-80 minutes. Finally, the base polyimide film is removed by keeping that temperature for 30-40 minutes, leaving only the ceramic metal oxide film formed on the surface, thereby obtaining a wrinkled ceramic nanosheet.

[0012] Preferably, in step (1), the thickness of the polyimide film used is 0.015 to 0.025 micrometers; the surface is cleaned with alcohol and deionized water for 1 to 3 times in sequence to remove oil and impurities on the surface of the film.

[0013] Preferably, in step (2), the concentration of the 2.5 mol / L sodium hydroxide solution used is 1.5 to 2.5 mol / L, and the polyimide film is immersed in the sodium hydroxide solution for 1 to 3 hours.

[0014] Preferably, Na + After being introduced into the surface of the polyimide film, it is washed with deionized water until it becomes neutral.

[0015] Preferably, in step (2), the metal salt solution is aluminum chloride solution, zirconium oxynitrate solution or magnesium nitrate solution.

[0016] Preferably, the metal salt solution is an aluminum chloride solution, and the concentration of the aluminum chloride solution is 0.2-0.5 mol / L.

[0017] Preferably, the ion exchange time is 0.5 to 2 hours. 3+ Introduced into the polyimide film surface.

[0018] Preferably, deionized water is used to wash away the AlCl 3 The solution was dried and then heated from room temperature to 300°C at a rate of 2°C / min and kept for 30 minutes to facilitate the formation of a ceramic aluminum oxide film on the surface of the polyimide film.

[0019] Preferably, after the ceramic aluminum oxide film is formed, the temperature is raised to 500° C. at a rate of 5° C. / min and kept at that temperature for 60 minutes, and finally kept at 600° C. for 30 minutes to remove the base polyimide film.

[0020] The field of dielectric energy storage is one of the main application areas of two-dimensional nanosheets. Two-dimensional nanosheets are introduced into polymers to form dielectric composite films. Since the surface area of ​​the corrugated structure is larger than that of the planar structure, the interface polarization effect is enhanced, and the gradient increase of the dielectric constant can be achieved. And due to the high insulation of the nanosheets and the greater obstruction of the breakdown path by the corrugated structure compared to the planar structure, the breakdown strength can be significantly enhanced, and finally the synergistic improvement of the dielectric constant and the breakdown strength can be achieved.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention prepares a wrinkled nanosheet, adopts a preparation strategy with relatively simple principle and process, has controllable content and is easy to operate, and the prepared nanosheet has stable quality, which is convenient for mass production.

[0023] The present invention obtains ultra-thin, ultra-large area wrinkled ceramic nanosheets through simple processes such as ion exchange and heat treatment, and introduces them into polymer dielectrics as fillers to achieve a synergistic improvement in dielectric constant and breakdown strength, thereby significantly improving energy storage performance. 2 O 3 Nanosheets are introduced into polymers as fillers to form nanocomposite films. The breakdown strength of the composite films at room temperature, 150°C, and 200°C has been significantly improved, reaching up to 780MV / m, 735MV / m, and 680MV / m, which are equivalent to 144%, 163%, and 170% of pure polymers, respectively, and can achieve a significant improvement in energy storage performance.

[0024] The method of the invention has strong versatility and can prepare nanosheets of various metal oxides with similar morphologies according to the activity of metals. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Flow chart of the preparation method of Example 1 of the present invention.

[0026] Figure 2 a is fold Al 2 O 3 Scanning electron microscope image of nanosheets. Figure 2 b is fold Al 2 O 3 EDX spectrum of nanosheets. Figure 2 c is wrinkled Al 2 O 3 Nanosheet X-ray photoelectron spectrum, Figure 2 d is the wrinkle Al 2 O 3 Atomic force microscopy image of the nanosheet.

[0027] Figure 3 a, 3b are folds Al at different magnification levels 2 O 3 Transmission electron microscopy image of the nanosheets; Figure 3 c is wrinkled Al 2 O 3 Selected area electron diffraction pattern of the nanosheets.

[0028] Figure 4 For wrinkled Al 2 O3 Dielectric constant and loss (a), breakdown strength (b) and discharge energy density (c) of WAO / PEI (hereinafter referred to as WAO / PEI) composite film at room temperature.

[0029] Figure 5 a. breakdown strength; b. discharge energy density of WAO / PEI composite films at 150°C; c. breakdown strength; d. discharge energy density at 200°C.

[0030] Figure 6 a. Power density of WAO / PEI composite film; b. Cyclic charge and discharge; c. Leakage current density.

[0031] Figure 7 a is a scanning electron microscope image of wrinkled MgO nanosheets; 7b is a scanning electron microscope image of wrinkled ZrO 2 Scanning electron microscopy image of the nanosheets.

[0032] Figure 8 Comparison of discharge energy density of WAO / PEI, WZO / PEI, and WMO / PEI composite films. DETAILED DESCRIPTION

[0033] The drawings are only used for illustrative purposes; for those skilled in the art, some well-known structures and their descriptions in the drawings may be omitted, and therefore, they should not be understood as limitations on the present invention.

[0034] Unless otherwise specified, the chemical substances and instruments used in the present invention can be obtained through conventional commercial channels.

[0035] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments to facilitate understanding of the technical solution of the present invention.

[0036] Example 1

[0037] like Figure 1 As shown, a method for preparing a wrinkled ceramic nanosheet, preparing a wrinkled ceramic Al 2 O 3 The membrane comprises the following steps:

[0038] (1) First, a 0.025 μm thick polyimide (PI) film was cut into square pieces and washed with alcohol and deionized water in turn to remove oil and impurities on the film surface;

[0039] (2) The PI film was immersed in a 2.5 mol / L sodium hydroxide (NaOH) solution for 2 hours to open the imide ring on the polyimide surface and + The PI film was then washed with deionized water until it was neutral and immersed in 0.5 mol / L aluminum chloride (AlCl 3) solution for 1 hour to carry out ion exchange, and Al 3+ Introduced into the film surface;

[0040] (3) Wash off the AlCl on the film surface with deionized water 3 The solution was dried and heated from room temperature to 300°C at a rate of 2°C / min for 30 minutes to facilitate the ceramic alumina (Al 2 O 3 ) film was formed, and then the temperature was raised to 500℃ at a rate of 5℃ / min and kept at this temperature for 60 minutes. Finally, the substrate PI film was removed at 600℃ for 30 minutes, leaving only the ceramic Al generated on the surface. 2 O 3 membrane.

[0041] like Figure 2 As shown, Figure 2 a, 2b are wrinkled Al 2 O 3 Scanning electron microscope image of the nanosheet and its EDX spectrum. From the image we can see that at the micrometer scale, the nanosheet has an irregular wrinkled structure. Figure 2 c is the wrinkle Al 2 O 3 Nanosheet X-ray photoelectron spectrum, from which we can see Al 2 O 3 The photoelectron spectrum of Al2p energy level shows a peak at 74.6eV. Figure 2 a, 2b, 2c can prove that the wrinkle Al 2 O 3 The nanosheets were successfully prepared. Figure 2 d Left is wrinkled Al 2 O 3 Atomic force microscopy images of the nanosheets further confirmed the wrinkled structure of the nanosheets. Figure 2 d Right is the height distribution map derived from the atomic force microscope analysis software, which characterizes the size and thickness of the nanosheet. The nanosheet is about ten microns wide and about twenty nanometers thick.

[0042] like Figure 3 As shown, Figure 3 a, 3b show the wrinkles of the nanosheet at the nanoscale, and it can be seen that the wrinkles are nanoscale. Figure 3 The selected area electron diffraction pattern of c shows that due to the low heat treatment temperature, this wrinkled Al 2 O 3 Nanosheets are a type of amorphous ceramic nanosheets.

[0043] like Figure 4As shown, before the dielectric properties test, we will perform open circuit / short circuit compensation on the LCR precision analyzer (E4980A) and test the dielectric properties of the material at room temperature of 100hz-1Mhz. The following formula (ε r =tC / Aε 0 ) to calculate the dielectric constant of the material, where t represents the sample thickness, A represents the electrode area, C represents the parallel capacitance, and ε 0 The absolute dielectric constant of free space is usually 8.85×10 -12 F / m. Figure 4 a shows the dielectric constant and dielectric loss of the composite film as a function of frequency. 2 O 3 The dielectric constant of the composite films with nanosheet contents of 0.1wt%, 0.2wt%, 0.3wt%, and 0.4wt% increases with the wrinkling Al 2 O 3 The increase of nanosheet content gradually increases. Although only a very small amount of 0.4wt% wrinkled Al 2 O 3 Nanosheets, the dielectric constant of the composite film is still increased by 44%. This is mainly attributed to two points: one is that the dielectric constant of aluminum oxide is relatively high (about 10), and the other is that the electric field is usually concentrated at the edge of the filler with higher curvature, which increases the stability of the carriers in this area. Aluminum oxide, as a highly insulating filler, will weaken the local electric field concentration inside the film, thereby reducing the number of carriers. Therefore, the electric field in the wrinkles and curved parts is higher than other areas, and the polarization rate at the wrinkles with larger curvature is higher, which increases the dielectric constant of the film.

[0044] For the breakdown strength test, we tested it with a ferroelectric tester (PK-CPE1801). The voltage rise rate was set to 500V / s, and finally the breakdown strength of the sample was obtained. Figure 4 b is the breakdown strength of WAO / PEI composite film at room temperature, which shows that its breakdown strength is greatly improved. 2 O 3 When the nanosheet contents were 0.1wt% and 0.2wt%, their breakdown field strengths reached 693.0MV / m and 797.4MV / m, which were 126.5% and 145.5% (548.0MV / m) of pure PEI, respectively.

[0045] like Figure 5As shown in Figures 5a and 5c, at high temperatures (150°C and 200°C), the breakdown strength of the 0.2wt% WAO / PEI composite film is 731.3MV / m and 684.5MV / m, reaching 158.1% and 158.3% of the pure PEI film, respectively. The significant improvement in breakdown performance is mainly attributed to two points. On the one hand, alumina is a highly insulating and highly thermally conductive ceramic material. The addition of this highly insulating and highly thermally conductive material to PEI improves the breakdown strength of the composite film at room temperature and high temperature. On the other hand, the ultra-thin and ultra-large wrinkled nanosheets in the matrix effectively prolong the development of electrical dendrites and hinder carrier transport. This is also the main reason why the breakdown strength of the composite film is improved at both room temperature and high temperature. The wrinkled structure increases the specific surface area of ​​the nanosheet. Compared with the nanosheet with a planar structure, the wrinkled structure makes the propagation path of the electrical dendrites more tortuous, and the thickness of the nanosheet is very thin (about 20 nanometers). There are a large number of wrinkles with different curvatures on the surface of the nanosheets. The high-curvature wrinkles prevent the propagation of the breakdown path, and the low-curvature wrinkles extend the extension path of the electric tree, which effectively dissipates the electrostatic energy under high electric fields, thereby improving the breakdown strength. However, with the increase in the mass fraction of fillers, the breakdown strength of the composite film first increases and then decreases. This may be due to the excessive amount of nanofillers causing agglomeration, resulting in stress concentration and the formation of defective areas, which leads to a significant deterioration of the breakdown performance, even less than the breakdown strength of pure polymers.

[0046] The hysteresis loop of the material was obtained using a ferroelectric tester (PK-CPE1801, poly-k Technologies), and the charge and discharge energy density and efficiency were obtained from the hysteresis loop. Figure 4 c, 5b, and 5d are the discharge energy density and charge-discharge efficiency diagrams of the composite film at room temperature and high temperature, respectively. Compared with the pure PEI film, the wrinkled Al 2 O 3 The energy storage density of the composite film of nanosheets changes according to the trend of breakdown strength, showing an increase first and then a decrease. The maximum energy storage density can reach 13.5 J / cm at room temperature, 150°C, and 200°C, respectively. 3 、10.1J / cm 3 , 8.0J / cm 3 ; We can intuitively see that the wrinkled Al 2 O 3 The discharge efficiency of the nanosheets is also improved under the same electric field.

[0047] like Figure 6 a, 6b are the power density diagram and charge-discharge cycle stability diagram of the composite film, respectively. 2 O 3 The composite film of nanosheets has a power density of up to 1.16MW / cm at 200℃ 3, and it remains stable after 50,000 cycles of charge and discharge under an electric field of 300MV / m. Figure 6 c is the leakage current density of the composite film at 200°C. Due to the insulation and thermal conductivity of aluminum oxide, as well as its blocking and scattering effects on electron transmission, the leakage current density of the composite film is also significantly reduced.

[0048] Example 2

[0049] The wrinkled MgO nanosheets were prepared using a magnesium nitrate solution, and the preparation method was the same as that in Example 1.

[0050] Cut a 0.025 μm thick polyimide (PI) film into square pieces and wash them with alcohol and deionized water in turn to remove oil and impurities on the film surface;

[0051] (2) The PI film was immersed in a 2.5 mol / L sodium hydroxide (NaOH) solution for 2 hours to open the imide ring on the polyimide surface and + The PI membrane was then washed with deionized water until it was neutral, and then immersed in a 0.5 mol / L magnesium nitrate solution for 1 hour for ion exchange. 2+ Introduced into the film surface;

[0052] (3) The magnesium nitrate solution on the surface of the film was washed off with deionized water. After drying, the temperature was increased from room temperature to 300°C at a rate of 2°C / min and kept for 30 minutes to facilitate the formation of a ceramic magnesium oxide film. The temperature was then increased to 500°C at a rate of 5°C / min and kept for 60 minutes. Finally, the substrate PI film was removed by keeping the temperature at 600°C for 30 minutes, leaving only the ceramic MgO film generated on the surface.

[0053] Other unmentioned places are the same as those in Example 1.

[0054] Example 3

[0055] Preparation of wrinkled ZrO using zirconium oxynitrate solution 2 The nanosheets are prepared in the same manner as in Example 1. (Zirconium oxynitrate is less soluble in water than magnesium nitrate and aluminum chloride, and if necessary, ultrasound should be used to dissolve the zirconium oxynitrate to form a uniform solution).

[0056] Other matters not involved are the same as those in Example 1.

[0057] like Figure 7 As shown in Figures 7a and 7b, they are scanning electron microscope images of wrinkled magnesium oxide (WMO) and wrinkled zirconium oxide (WZO) metal oxide ceramic wrinkled nanosheets with similar morphology, respectively, prepared by the same method. Obvious wrinkles can be seen in the images.

[0058] like Figure 8As shown, when the mass fraction of metal oxide ceramic wrinkled nanosheets is 0.2wt%, the WZO / PEI composite film and WMO / PEI composite film have excellent energy storage performance at 150°C, just like the WAO / PEI composite film, which once again proves the versatility, stability and role of the wrinkled structure of this method.

[0059] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a wrinkled ceramic nanosheet, characterized in that: The steps include: (1) Cut the polyimide film into square pieces, clean the surface, remove impurities and set aside; (2) Using polyimide film as the matrix, immerse the polyimide film in a sodium hydroxide solution to open the imide ring on the polyimide surface and convert the Na + The polyimide film is then washed with water and immersed in a metal salt solution for ion exchange to introduce metal ions into the film surface; (3) Cleaning: The film finally obtained in step (2) is dried and heated from room temperature to 250-350°C at a rate of 1-3°C / min and kept at that temperature for 20-40 minutes to facilitate the formation of a ceramic metal oxide film. The temperature is then raised to 500-700°C at a rate of 4-6°C / min and kept at that temperature for 60-80 minutes. Finally, the base polyimide film is removed by keeping at that temperature for 30-40 minutes, leaving only the ceramic metal oxide film formed on the surface, thereby obtaining wrinkled ceramic nanosheets.

2. The method for preparing a wrinkled ceramic nanosheet according to claim 1, characterized in that: In the step (1), the thickness of the polyimide film used is 0.015 to 0.025 micrometers; the surface is cleaned with alcohol and deionized water for 1 to 3 times in sequence to remove oil and impurities on the surface of the film.

3. The method for preparing a wrinkled ceramic nanosheet according to claim 1, characterized in that: In the step (2), the concentration of the 2.5 mol / L sodium hydroxide solution used is 1.5 to 2.5 mol / L, and the polyimide film is immersed in the sodium hydroxide solution for 1 to 3 hours.

4. The method for preparing a wrinkled ceramic nanosheet according to claim 3, characterized in that: Na + After being introduced into the surface of the polyimide film, it is washed with deionized water until it becomes neutral.

5. The method for preparing a wrinkled ceramic nanosheet according to claim 1, characterized in that: In the step (2), the metal salt solution is an aluminum chloride solution, a zirconium oxynitrate solution or a magnesium nitrate solution.

6. The method for preparing a wrinkled ceramic nanosheet according to claim 5, characterized in that: The metal salt solution is an aluminum chloride solution, and the concentration of the aluminum chloride solution is 0.2-0.5 mol / L.

7. The method for preparing a wrinkled ceramic nanosheet according to claim 6, characterized in that: The ion exchange time is 0.5 to 2 hours. 3+ Introduced into the polyimide film surface.

8. The method for preparing a wrinkled ceramic nanosheet according to claim 7, characterized in that: The AlCl3 solution on the surface of the film was washed off with deionized water, and after drying, the temperature was raised from room temperature to 300°C at a rate of 2°C / min and kept for 30 minutes to facilitate the formation of a ceramic aluminum oxide film on the surface of the polyimide film.

9. The method for preparing a wrinkled ceramic nanosheet according to claim 8, characterized in that: After the ceramic alumina film is formed, the temperature is raised to 500°C at a rate of 5°C / min and kept for 60 minutes, and finally kept at 600°C for 30 minutes to remove the substrate polyimide film and retain the ceramic alumina film.